The drama of dictatorship martial law and the communist parties of the Philippines - Scalice, Joseph 1976- (Southeast Asia Program Publications, an imprint of Cornell University Press, 2023)
"The first attempt in English -- indeed, in any language -- to write the history of how Marcos was able to impose a military dictatorship on the Philippines, arguing that it was the rivalry between the two Stalinist parties -- the PKP and the CPP -- that facilitated and enabled Marcos' consolidation of power"--